Description of Students' Critical Thinking Skills in Solving Open Ended Problems Based on Their Learning Style - Rosidah; Sabri; Ilmi, Nur (ARRUS Journal of Mathematics and Applied Science, 2021)
This study aims to know the description of students' critical thinking skills in solving mathematical problems through open-ended questions investigated on the base of learning styles. The study is descriptive research employing a qualitative approach. There were six research subjects, namely, two students with visual learning styles, two students with auditory learning styles, and two students with kinesthetic learning styles. The instruments used were written tests, a questionnaire, and an interview guide. The results showed that the students with a visual learning style were able to fulfil indicators at the stages of providing simple explanations, building basic skills, arranging strategies and tactics, and drawing conclusions. Further, the students with an auditory learning style were less able to fulfil indicators at the stages of providing simple explanations. They were not able to fulfil indicators at the stage of managing strategies and tactics, as well as drawing conclusions; yet, they were able to fulfil indicators at the stage of building basic skills. And, the students with a kinesthetic learning style were less able to fulfil indicators at the stage of providing simple explanations; moreover, they were not yet able to fulfil indicators at the stages of building basic skills, managing strategies and tactics, as well as drawing conclusions.